The Islamic Religious Education Curriculum Towards Globalization of Education: A Study on the Dynamics and Implications of Curriculum Changes - Putri, Luqyana Azmiya; Hamami, Tasman (UIII Press, 2023)
The quality of education is closely related to the curriculum that is implemented. Due to the consequences of changes in political, social, cultural, economic and technological systems, the curriculum also undergoes changes. Since Indonesia’s independence in 1945, the country has developed and been implementing its own school curriculum starting in 1947, 1952, 1964, 1968, 1975, 1984, 1994, 1999, 2004, 2006, and 2013. This study aims to analyze the dynamics and implications of curriculum changes in Islamic education and to examine its existence in the globalization of education. The research method used a library research approach with data analysis techniques including data reduction, data presentation and conclusion drawing. The results show that Islamic education has been implemented since the independence era, albeit influenced by the Dutch at that time. After the era of independence and reformation, the changes in curriculum resulted in the government giving special attention to Islamic Religious Education (called as PAI), which was demonstrated by the establishment of Islamic institutions called “madrasa” and Islamic universities. Indonesia’s experience in various curriculum models is a strength in exploring the potential of Islamic education to adapt to the discourse of global education. Moreover, Islamic education in Indonesia has the opportunity to become a world leader. To achieve this, efforts are needed to strengthen the Islamic education system and its curriculum, expand access to information and communication technology, improve the quality of teachers and researchers through increasing academic qualifications, and build international cooperation with other countries in the form of curriculum development and scholarships for foreign students who want to study PAI.